(untitled) (CIPEEX, 2025)
Syphilis is a sexually transmitted infection (STI) caused by the bacterium Treponema pallidum. Transmission occurs mainly through sexual contact, but can also be vertical during pregnancy or through blood transfusion. Brazil is facing a syphilis epidemic, making it essential to identify, treat, and educate the population about preventive measures. Thus, this study aimed to assess the level of knowledge about syphilis in the population served by the BHUs (Basic Health Units), also called UBSs (Unidade Básica de Saúde) in Brazil, in the Northwest region of Anápolis-GO. This is an observational, cross-sectional, and descriptive study in which a questionnaire was applied to the population that sought care at the UBS during the year 2023. The UBSs surveyed were selected through random sampling. Data from 70 participants were collected, 71.4% of whom were female. The overall average age was 42 years (±16.3). Regarding knowledge, 77.1% stated that they knew what syphilis is. Regarding the etiological agent of the disease, 24.3% responded that syphilis is caused by bacteria. Regarding transmission, 84.3% responded that it is transmitted through sexual contact. It was concluded that the majority of study participants were female, between 18 and 39 years of age. Most were incorrect about the etiological agent of syphilis, with 38.5% choosing the option “virus.” In addition, 70% of participants correctly identified the initial clinical manifestation of the disease and understood that the main form of prevention is condom use. Despite this, many did not use condoms, especially those with multiple partners or in relationships with steady partners.